In search of features that constitute an “enriched environment” in humans: Associations between geographical properties and brain structure - Simone Kühn; Sandra Düzel; Peter Eibich; Christian Krekel; Henry Wüstemann; Jens Kolbe; Johann Martensson; Jan Goebel; Jürgen Gallinat; Gert G. Wagner; Ulman Lindenberger (Scientific Reports, 2017)
Enriched environments elicit brain plasticity in animals. In humans it is unclear which environment is enriching. Living in a city has been associated with increased amygdala activity in a stress paradigm, and being brought up in a city with increased pregenual anterior cingulate cortex (pACC) activity. We set out to identify geographical characteristics that constitute an enriched environment affecting the human brain. We used structural equation modelling on 341 older adults to establish three latent brain factors (amygdala, pACC and dorsolateral prefrontal cortex (DLPFC)) to test the effects of forest, urban green, water and wasteland around the home address. Our results reveal a significant positive association between the coverage of forest and amygdala integrity. We conclude that forests may have salutogenic effects on the integrity of the amygdala. Since cross-sectional data does not allow causal inference it could also be that individuals with high structural integrity choose to live closer to forest.
Keywords: 330; Development of the nervous system; Environmental impact; Learning and memory